Interface processes between protected and unprotected areas: A global review and ways forward. (7th November 2019) - Blanco, Julien; Bellón, Beatriz; Fabricius, Christo; de O. Roque, Fabio; Pays, Olivier; Laurent, François; Fritz, Hervé; Renaud, Pierre‐Cyril
Abstract: Land‐use changes and the expansion of protected areas (PAs) have amplified the interaction between protected and unprotected areas worldwide. In this context, 'interface processes' (human–nature and cross‐boundary interactions inside and around PAs) have become central to issues around the conservation of biodiversity and ecosystem services. This scientific literature review aimed to explore current knowledge and research gaps on interface processes regarding terrestrial PAs. At first, 3, 515 references related to the topic were extracted through a standardized search on the Web of Science and analyzed with scientometric techniques. Next, a full‐text analysis was conducted on a sample of 240 research papers. A keyword analysis revealed a wide diversity of research topics, from 'pure' ecology to sociopolitical research. We found a bias in the geographical distribution of research, with half the papers focusing on eight countries. Additionally, we found that the spatial extent of cross‐boundary interactions was rarely assessed, preventing any clear delimitation of PA interactive zones. In the 240 research papers we scanned, we identified 403 processes that were studied. The ecological effects of PAs were well documented and appeared to be positive overall. In contrast, the effects of PAs on local communities were understudied and, according to the literature focusing on these, were very variable according to local contexts. Our findings highlight key research advances on interface processes, especially regarding the ecological outcomes of PAs, the influence of human activities on biodiversity, and PA governance issues. In contrast, main knowledge gaps concern the spatial extent of interactive zones, as well as the interactions between local people and conservation actions and how to promote synergies between them. While the review was limited to terrestrial PAs, its findings allow us to propose research priorities for tackling environmental and socioeconomic challenges in the face of a rapidly changing world. Abstract : Interface processes encompass human–nature and cross‐boundary interactions inside and around protected areas (PAs) and play a key role on the ecological and socioeconomic outcomes of PAs. Through a standardized review, we found that literature on interface processes was dominated by biophysical approaches that emphasized the negative influence of humans on ecosystems and the ecological benefits of PAs, while social and social–ecological approaches were underrepresented. Further research should focus on assessing the multidirectional and multiscale interactions between people and PAs and delineating the spatial extent of the zones that interact with PAs, two key challenges for improving conservation in the Anthropocene.